THE EFFECT OF PROVINCIAL MINIMUM WAGES, INFLATION AND TOTAL POPULATION ON ECONOMIC GROWTH IN WEST SUMATRA PROVINCE, 2010-2021 - Muhamad Sidiq Abdillah; Reza Juanda; Rico Nur Ilham (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study aims to determine the effect of the Provincial Minimum Wage, Inflation, and Population on Economic Growth in West Sumatra Province. The data used in this research is secondary data from 2010-2021. To reach the research object using multiple linear regression analysis method. The results of this study partially indicate that the provincial minimum wage variable has a positive and significant effect on economic growth in West Sumatra Province, the inflation variable has no effect and is not significant on economic growth and the population variable has a negative and significant effect on economic growth in West Sumatra Province. While simultaneously the variables of the provincial minimum wage, inflation, and population have a positive and significant effect on economic growth in West Sumatra Province. The coefficient of determination ( in this study is 0.988861, which means that the effect of the provincial minimum wage, inflation and population on economic growth is 0.988861 or 98.88% while the remaining 1.12% is influenced by other variables outside this study.